Penerapan Metode Irigasi Tetes Guna Mendukung Kegunaaan Air yang Efisien di Desa Ketangga Kecamatan Suwela Kabupaten Lombok Timur - Hermawan, Hendri; Alawiyah, Tutik; Imani, Nuansa Putty; Saidah, Humairo; Irawan, Almira Ursula; Zamharia, Martiana; Ardhanareswari, Putu Diah; Aini, Rohadatul; Kencana, Ida Bagus Adi; Natalia, Elya; Widyasari, Ni Made Cahya Devi (Universitas Mataram, 2024)
Water scarcity and rainfall uncertainty in Ketangga Village is one of the adversities in developing rainfed agriculture. This condition causes the agricultural land then more often left not planted during the dry season. Ketangga Village is located on the slopes of Mount Rinjani and has very fertile land and the best quality agricultural products. For this reason, the Mataram University Real Work Lecture Team (K.K.N.) held the introduction of Drip Irrigation to the Swela Village community so that villagers can still grow crops even with limited water. The activity was carried out in two stages, namely socialization, whereby resource persons from agricultural extension workers were presented, and drops of irrigation demonstrations were made on the land of one of the residents. Counseling and demonstrations have been carried out and are running well. The community was very enthusiastic about welcoming this activity, as seen from the many participants who attended counseling. The Swela community feels happy because those who previously did not know about drip irrigation technology now know how to make their drips using simple and accessible materials to find in the market. While spreading information about appropriate technology for agriculture businesses on dry land, this activity is also expected to stimulate community creativity in overcoming difficulties in providing irrigation water for their agricultural businesses.